Using Cost-Effective Surveys From Platforms of Opportunity to Assess Cetacean Occurrence Patterns for Marine Park Management in the Heart of the Coral Triangle - Sahri, Achmad; Mustika, Putu Liza Kusuma; Purwanto, Purwanto; Murk, Albertinka J.; Scheidat, Meike (Frontiers in Marine Science, 2020)
The Wakatobi National Park (WNP) at the heart of Coral Triangle is an important area for cetaceans in Indonesia. Currently there is insufficient information on spatio-temporal occurrence patterns of cetaceans to inform effective conservation strategies. This study used platforms of opportunity from May 2004 to May 2012 as a cost-effective way to address this knowledge gap. A database was created of cetacean sightings per surveyed days at sea, allowing for an analysis of species diversity and habitat use around the islands. A total of 11 cetacean species were identified. Spinner and bottlenose dolphins were sighted most often, followed by melon-headed and sperm whales. Spinner dolphin showed a wide distribution in the area, whilst bottlenose dolphin and melon-headed whale occupied the waters between the main islands and south atolls. Sperm whales occurred mostly in waters to the north of the main islands and as melon-headed whales were mostly found in deep waters. Most cetacean sightings occurred in the zones designated for human use, indicating where potential conflicts might occur. No sightings were found in the Park core zone, indicating a mismatch between WNP design and the ecological needs of the cetaceans. A sub-sample of the data from dedicated fishing monitoring trips was used to derive a sighting frequency. Occurrence of both small and large cetaceans was highest during inter-monsoonal seasons, possibly related to an increase of prey availability due to seasonal upwelling and increase in survey activity. Inter-annual occurrence of cetaceans was variable, with no large cetaceans being sighted in 2010-2012, likely due to reduced survey efforts. In areas with limited resources for designated surveys, the use of platforms of opportunity can be a cost-effective tool to provide valuable data on cetacean occurrence. It helps identify potentially important areas as well as highlight where to direct designated research efforts. We discuss the implications of our findings for the conservation management of these cetaceans and give suggestions for improved marine park management.